The baseline is already shifted: marine microbiome restoration and rehabilitation as essential tools to mitigate ecosystem decline - Raquel S. Peixoto; Christian R. Voolstra (Frontiers in Marine Science, 2023)
Climate change is turning formerly pristine ecosystems into ever-changing states, causing major disturbance and biodiversity loss. Such impacted marine ecosystems and organisms exhibit clear microbiome shifts that alter their function. Microbiome-targeted interventions appear as feasible tools to support organismal and ecosystem resilience and recovery by restoring symbiotic interactions and thwarting dysbiotic processes. However, microbiome restoration and rehabilitation are perceived as drastic measures, since they alter ‘natural relationships’. What is missing from this notion is that microbiomes already drastically differ from any pre-anthropogenic state. As such, our perception and definition of even ‘pristine states’ may in fact represent an already disturbed/derived condition. Following this, we argue that restoring and rehabilitating marine microbiomes are essential tools to mitigate ecosystem and organismal decline.